Implementation and Evaluation of Evidence-Based Psychotherapeutic Practices for Youth in a Mental Health Organization. - Bloomquist, Michael; Giovanelli, Alison; Benton, Anna; Piehler, Timothy; Quevedo, Karina; Oberstar, Joel (Journal of Child & Family Studies, 2016)
The current initiative and program evaluation study is a demonstration of the research to practice process in youth-focused psychotherapy. We collaborated within a community-university partnership to create practice and research infrastructure in order to develop, implement, and evaluate two new models of service founded on evidence-based psychotherapeutic practice parameters. The two new service models incorporated validated interventions to address behavior problems in elementary age children, and depression in adolescents, which were delivered in separate but similarly run intensive outpatient programs within a mental health setting. We utilized a rigorous training, technical assistance, fidelity monitoring, and outcome measurement strategy to promote the integrity and quality of services provided. The resultant programs were delivered with acceptable to high fidelity and effects on youth and parenting measures collected during program and from pre to post showed a decrease in targeted problems in youth and positive benefits for families. This initiative and program evaluation adds to the accumulating research-to-practice literature in children's mental health.